Carbon-titanium dioxide heterogeneous (photo)catalysts (C–TiO2) for highly efficient visible light photocatalytic application. (15th July 2022) - Lim, Chaehun; An, Ha-Rim; Lee, Hyeryeon; Lee, Raneun; Choi, Yunju; Park, Ji-In; Yoon, Jeechan; Lee, Hyun Uk; Lee, Young-Seak
Abstract: In this paper, a novel one-step method for the synthesis of a heterogeneous carbon-titanium dioxide (photo)catalyst (C–TiO2 ) is first reported. This synthesis method was performed at room temperature and atmospheric pressure using underwater plasma treatment for 15 min over various ratios of titanium and carbon sources. The resulting C–TiO2 had anatase/brookite polycrystalline phases with turbostratic carbon and large surface areas. The bandgap energies were narrowed by the generation of reactive oxygen species and carbon bonds in the lattice of TiO2, extending optical absorption into the visible range. C60–TiO2, which had optimal ratios of carbon and TiO2, exhibited superior photocatalytic activities for methylene blue ([ k ] = 4.61 h −1 ) under artificial solar irradiation due to its enhanced optical properties and numerous adsorption sites, which were approximately 10 times higher than those of commercial TiO2 ([ k ] = 0.41 h −1 ). This study represents a milestone of rapid and convenient methods to produce C–TiO2 with high photocatalytic performance for environmental applications.